The Effectiveness of Using Visual Media in Improving Learning Outcomes on the Pillars of Islam Material at SD Negeri 0102 Sibuhuan - Hasibuan, Donni Maspuan; Nasution, Irdani Waridah (Jurnal Cendekia Islam Indonesia, 2025)
This Classroom Action Research (CAR) aims to determine the effectiveness of using visual media in improving the learning outcomes of grade 3 elementary school students on the Pillars of Islam material at SD Negeri 0102 Sibuhuan. The problem faced is the low learning outcomes of students in understanding and practicing the Pillars of Islam material, which can be seen from the low test scores and the lack of interest and participation of students in learning activities. Therefore, this study uses visual media as an effort to improve student understanding. The design of this study is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data were collected through observation, interviews, and learning outcome tests. Data analysis was carried out by comparing student learning outcomes before and after the use of visual media in learning. The results of the study showed that the use of visual media can improve students' understanding and learning outcomes on the Pillars of Islam material. This is indicated by an increase in the average score of student learning outcomes tests in the second cycle, as well as an increase in students' active participation in discussions and learning activities. Based on these findings, it is recommended that the use of visual media be introduced and used routinely in learning, especially on materials that require concrete understanding such as the Pillars of Islam.